1987
DOI: 10.1177/001979398704000201
|View full text |Cite
|
Sign up to set email alerts
|

Congressional Voting on Labor Issues: The Role of PACS

Abstract: This study measures the impact of labor and corporate political action committee (PAC) contributions on the voting of members of the House of Representatives on labor issues during 1979–80. It also analyzes the allocation of labor PAC contributions among House candidates. PAC contributions were found to have a significant direct effect on roll-call voting, even controlling for the Representative's political party and characteristics of the constituency. Since PAC money also affects roll-call voting indirectly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(15 citation statements)
references
References 6 publications
1
14
0
Order By: Relevance
“…16-17). Some studies have found a significant, positive relationship (Frendreis and Waterman, 1985;Saltzman, 1987;Wilhite and Theilmann, 1987) while other studies found no effect (Chappell, 1981;Grenzke, 1989b;Welch, 1982). Conflicting findings are explained by the fact that the money-vote relationship is complicated (Snyder, 1992, p. 17).…”
Section: Effectiveness Of Financial Tacticsmentioning
confidence: 99%
“…16-17). Some studies have found a significant, positive relationship (Frendreis and Waterman, 1985;Saltzman, 1987;Wilhite and Theilmann, 1987) while other studies found no effect (Chappell, 1981;Grenzke, 1989b;Welch, 1982). Conflicting findings are explained by the fact that the money-vote relationship is complicated (Snyder, 1992, p. 17).…”
Section: Effectiveness Of Financial Tacticsmentioning
confidence: 99%
“…In considering this phenomenon, researchers have identified two different strategies that PACs pursue when contributing to candidates (Conway 1991). First, some PACs follow an access strategy which involves targeting funds to those candidates who have leadership positions or committee jurisdiction over legislation crucial to the group (Herndon 1982;Gopoian 1984Gopoian , 1985Wright 1985;Maitland 1985;Denzau and Munger 1986;Grier and Munger 1986Masters and Zardkoohi 1986;Langbein 1986Langbein , 1993Saltzman 1987;Langbein and Lotwis 1990;Grier, Munger, and Torrent 1990;Hall and Wayman 1990;Endersby and Munger 1992;Hurd and Sohl 1992). The second major strategy PACs follow is to target funds to those candidates who agree with them ideologically in order to get them elected.…”
Section: Previous Researchmentioning
confidence: 99%
“…5 Third, different regions of the country are affected differently by a trade policy, and senators recognize that the policy will lead to more or less business and employment in their state (Blake and Waiters, 1987). Winners and losers from trade policy are unevenly distributed so that constituent pressures vary by region (Saltzman, 1987). 6…”
Section: Ideologymentioning
confidence: 99%